Economic Jihad as a Normative Framework in Pesantren Economies: A Comparative Case Study in Madura - Ahmad Fadil; Sulhan (Musyarakah: Journal of Sharia Economic (MJSE), 2026)
Introduction/Main Objectives: This study explores the application of economic jihad in pesantren-based economic organizations and its impact on community empowerment and institutional governance. Due to the growing participation of pesantren in the Islamic economic system and the continuing lack of investigation into their economic practices, the subject is important. Background Problems: There is no study of how economic jihad is implemented across various pesantren governance models. The research question is: What does economic jihad mean, and how is it practiced in pesantren economic organizations?  Novelty: This work takes a comparative and analytical approach, in contrast to earlier descriptive investigations. The institutional variations of economic jihad and their consequences for governance and empowerment have not been sufficiently studied in any prior research. Research Methods: A qualitative comparative case study of two pesantren in Madura was done. Field observations and interviews were used to gather data, which was then analyzed to determine governance structures and economic behavior. Findings/Results: According to the study, economic jihad serves as a normative-economic framework that influences institutional behavior. Community empowerment is prioritized in a cooperative model, whereas institutional self-sufficiency is given more importance in a centralized model. The economic practices and social consequences are greatly impacted by the institutional structure. Conclusion: this study finds that in pesantren economic systems, integrating governance models improves sustainability and social effect. The major conclusion is that institutional design is essential to optimizing the effectiveness of economic jihad as a tool for governance and a method for empowering communities.